Assessment of prognostic factors for reconstruction of the upper third of the ureter with a tubularized pelvis flap - Demchenko, Vladyslav; Shchukin, Dmytro; Khareba, Gennadii; Antonyan, Igor; Maltsev, Andriy (ScienceRise: Medical Science, 2020)
Ureteral plastic with a tubularized pelvic flap is a rare option of ureteral reconstruction. We present the assessment of the factors that are important for predicting the success of this operation. The aim. The purpose of the study was to assess the factors that are important in predicting the success of reconstruction of the upper third of the ureter with a tubularized pelvis flap. Material and methods. The study included 73 patients who were divided into 2 groups. The first group had extended strictures of the upper third of the ureter (n=14 / 19.2 %), and the second group had pathology of the ureteropelvic junction associated with ureterovascular conflict (n=59 / 80.8 %). Results. The length of the pelvic flap varied from 2.5 to 10.0 cm and reached an average of 3.9 cm. Early postoperative complications (Clavien-Dindo gradation <3) were observed in 14 (9.2 %) patients out of 73, and dominated in the first group. The total number of positive long-term results (good + satisfactory) was 97.3 %. Two poor results were reported only in patients of the first group with prolonged recurrent strictures. A significant factor in the prognosis of complications was the secondary nature of the operation (p <0.004). The factors of the long-term results prognosis were the performance of dismembered tubularized flap pyeloplasty due to the extended strictures of the upper third of the ureter, and the duration of the operation more than 120 minutes (p <0.009 and p <0.026). Conclusion. Surgical correction of the upper third of the ureter by a tubularized pelvis flap is a highly effective and safe method of reconstruction of the upper urinary tract. The main negative factors in the prognosis of this operation results are the secondary nature of the operation, the performance of the dismembered tubularized flap pyeloplasty because of the extended strictures of the upper third of the ureter, and the duration of the operation more than 120 minutes